Trust factors in collaborative and shared knowledge management of the Museum Konperensi Asia-Afrika librarians - Silalahi, Reginawati; Winoto, Yunus; Khadijah, Ute Lies Siti (Jurnal Kajian Informasi dan Perpustakaan, 2026)
Background: This study highlights the significance of knowledge sharing in special libraries, particularly the library of the Museum Konperensi Asia-Afrika, for preserving information and enhancing service quality. Trust has been identified as a crucial factor facilitating knowledge sharing among librarians, creating an open and collaborative work environment. Purpose:  The objective of this study is to analyze the role of trust in supporting knowledge sharing among librarians at the library of the Museum Konperensi Asia-Afrika. Methods: A qualitative case study approach, involving in-depth interviews, literature review, and document analysis. Results: The findings reveal that trust among librarians fosters openness in sharing both explicit and tacit knowledge and cultivates a collaborative work climate. Moreover, strong trust enhances librarians' motivation to share knowledge, positively impacting the quality of services provided to library users. High-quality communication, solid professional experience, proven skills, and egalitarian organizational culture all contribute to strengthening this process by fostering transparency and mutual respect. Interactions, both formal and informal, play a vital role in maintaining collaboration and resolving problems. Conclusions: This study confirms that trust is an important factor in promoting effective knowledge sharing in Museum Konperensi Asia-Afrika library. Trust between librarians facilitates effective collaboration, an open work environment, and the exchange of technical and confidential knowledge. Implications: This study concludes that trust is a fundamental element in promoting effective knowledge sharing within the MKAA Library, enabling collaborative practices and the exchange of technical as well as sensitive information. The implications of this study are twofold: practically, it suggests that library management should prioritize trust-building strategies to enhance collaboration and service quality; theoretically, it contributes to knowledge management literature by emphasizing trust as a key social dimension in knowledge sharing within special library settings.